2006
DOI: 10.1063/1.2393161
|View full text |Cite
|
Sign up to set email alerts
|

Optical limiting behavior of bismuth oxide-based glass in the visible range

Abstract: The authors report experimental results on the optical limiting behavior of a bismuth oxide-based glass by exciting the samples with nanosecond laser pulses at 532 and 598 nm. The results show that two-photon and free-carrier absorption processes contribute for the nonlinear absorption. Values for ␤, the two-photon absorption coefficient, and e , the absorption cross section due to free carriers, were determined. The values of ␤ and e are dependent on the amount of bismuth oxide in the glass composition. © 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Nonlinear absorption can be exploited for optical limiting application, and we have shown in a separate publication that this glass is very suitable for such application, particularly in the nanosecond regime. 14 For the visible and near-infrared excitation wavelengths studied, the electronic nonlinearity is positive for all the materials, characteristic of self-focusing nonlinearity. In the picosecond regime, the measured nonlinear refractive index is higher for the BZH2 glass than for the BZH7 for both wavelengths.…”
Section: -3mentioning
confidence: 99%
“…Nonlinear absorption can be exploited for optical limiting application, and we have shown in a separate publication that this glass is very suitable for such application, particularly in the nanosecond regime. 14 For the visible and near-infrared excitation wavelengths studied, the electronic nonlinearity is positive for all the materials, characteristic of self-focusing nonlinearity. In the picosecond regime, the measured nonlinear refractive index is higher for the BZH2 glass than for the BZH7 for both wavelengths.…”
Section: -3mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10] In particular, compositions of HMO glasses containing lead and/or bismuth are strong candidates and have been studied in the past few years. [6][7][8][9][10] Recent measurements with bismuth oxide based glasses from the femtosecond to the nanosecond regime 6,7 demonstrated that the presence of heavy-metal atoms is very important to enhance the nonlinearity. Previous studies using pulses of 35 and 100 fs at wavelengths in the range of 600-1250 nm also revealed increasing of the HMO glasses nonlinearity with the increase of heavy-metal content.…”
mentioning
confidence: 99%
“…Among these various promising optical materials, oxide glasses containing heavy atomic (ionic) oxides, such as bismuthate, tellurite, or plumbum oxides, have stimulated great interest because they have the advantages of high chemical and thermal stability, simple fabrication process, low optical loss over large spectral ranges, and high optical damage threshold [9][10][11][12]. Particularly, many bismuth-based glasses with heavy atomic (ionic) oxides present large third-order optical nonlinearities for the applications in ultrafast all-optical switches [13], optical power limiters [14], and wavelength division multiplexing devices [15]. Recently, it was reported that the optical Kerr-gated (OKG) ballistic imaging employed a short time gate to visualize the object hidden in turbid media by selecting the ballistic and snake photons, and suppressing scattering photons, which were applied in investigating the characterization of turbid media such as biological tissue [16], fuel sprays [17], and liquid jets [18].…”
Section: Introductionmentioning
confidence: 99%